CsMYB5a and CsMYB5e from Camellia sinensis differentially regulate anthocyanin and proanthocyanidin biosynthesis. (May 2018) - Jiang, Xiaolan; Huang, Keyi; Zheng, Guangshun; Hou, Hua; Wang, Peiqiang; Jiang, Han; Zhao, Xuecheng; Li, Mingzhuo; Zhang, Shuxiang; Liu, Yajun; Gao, Liping; Zhao, Lei; et al.
Highlights: A total of 140 R2R3-MYBs were screened from different tea transcriptome databases. CsMYB5a reduced the accumulation of anthocyanin but promoted the accumulation of PAs. DMACA-stained PAs increased significantly in CsMYB5e-overexpressing tobacco flowers. Genes related to PA and anthocyanin biosynthesis pathways were markedly up regulated. 3 UGTs and 4 GSTs involved in anthocyanin glycosylation and transportation. Abstract: Tea is one of the most widely consumed nonalcoholic beverages worldwide. Polyphenols are nutritional compounds present in the leaves of tea plants. Although numerous genes are functionally characterized to encode enzymes that catalyze the formation of diverse polyphenolic metabolites, transcriptional regulation of those different pathways such as late steps of the proanthcoyanidin (PA) pathway remains unclear. In this study, using different tea transcriptome databases, we screened at least 140 R2R3-MYB transcription factors (TFs) and grouped them according to the basic function domains of the R2R3 MYB TF superfamily. Among 140 R2R3 TFs, CsMYB5a and CsMYB5e were chosen for analysis because they may be involved in PA biosynthesis regulation. CsMYB5a- overexpressing tobacco plants exhibited downregulated anthocyanin accumulation but a high polymeric PA content in the flowers. Overexpression of CsMYB5e in tobacco plants did not change the anthocyanin content but increased the dimethylaminocinnamaldehyde-stained PA content. RNA-seq and qRT-PCR analyses revealed that genes related to PA and anthocyanin biosynthesis pathways were markedly upregulated in both CsMYB5a - and CsMYB5e -overexpressing flowers. Three UGTs and four GSTs were identified as involved in PA and anthocyanin glycosylation and transportation in transgenic plants. These results provide new insights into the regulation of PA and anthocyanin biosynthesis in Camellia sinensis .